Anal Fissure: Is it becoming a medical disorder? - Al-shaham, Ali; Jawad, Kadhim; MS, Serene , A.A (AL-Kindy College Medical Journal, 2014)
An anal fissure which does not heal with conservative measures as sits baths and laxatives is a chronic anal fissure. Physiologically, it is the high resting tone of the internal anal sphincter that chiefly interferes with the healing process of these fissures. Until now, the gold standard treatment modality is surgery, either digital anal dilatation or lateral sphincterotomy. However, concerns have been raised about the incidence of faecal incontinence after surgery. Therefore, pharmacological means to treat chronic anal fissures have been explored.A Medline and pub med database search from 1986-2012 was conducted to perform a literature search for articles relating to the non-surgical treatment of chronic anal fissure.Pharmacological sphincterotomy using Glyceryl trinitrate , Isosorbide dinitrate or calcium channel blockers are exciting alternative treatment , that relaxes the anal sphincter and, therefore, promote healing, the drawback of such medications are headache and poor compliance. With the introduction of Botulinum toxin as mean of chemical sphincterotom, topical injection of Botulinum toxin reduces the anal hypertonia which lasts for few months, allows the fissure to heal, thus eliminating the need for surgery without incidence of incontinence. Cure rates are over 60%, and the procedure can be repeated safely. Therefore, Botulinum toxin is a reasonable first-line management of chronic anal fissure and the relapses can be managed by surgeryKeywords: Non-surgical treatment of anal fissure, fissure in ano, sphicterotomy,botulinum toxin in anal fissures, glyceryl trinitrate. Chemical sphincteratomy, pharmacological sphincteratomy.